Answer:
We need an image or more info
Step-by-step explanation:
Answer:
The correct answer is option B). 7x² -12x√14 + 72
Step-by-step explanation:
I<u>dentity</u>
(a - b)² = a² - 2ab + b²
Find the product
It is given that ( x√7 - 3√8)(x√7 - 3√8)
(x√7 - 3√8)(x√7 - 3√8) = (x√7 - 3√8)²
(x√7 - 3√8)² = (x√7)² - 2*x√7*3√8 +(3√8)²
= 7x² - 6x√56 + 72
= 7x² - 6x*2√14 + 72
= 7x² - 12x√14 + 72
Therefore the correct answer is option B). 7x² - 12x√14 + 72
Initial velocity (u) = 0m/s
Final velocity (v) = 20m/s
Time (t) = 10 s
Acceleration (a)
= (v - u)/t
= [(20m/s) - (0m/s)]/10s
= (20m/s)/10s
= (20m/s²)/10
=> 2m/s²
Answer:
False
Step-by-step explanation:
11 times 11 is 121
5 times 5 is 25
13 times 13 is 169
121+25 doesnt equal 169
this means it is not a right angled triangle as it does not follow pythag
Answer:
r = 8°
Step-by-step explanation:
95° = 6r° + 47° ( vertically opposite angles are equal)
6r° = 95° - 47°
6r = 48°
r = 48°/6
r = 8°